Self‐Healable and Recyclable Sulfur Rich Poly(vinyl chloride) by S–S Dynamic Bonding. Issue 1 (22nd January 2022) - Deliballi, Zeynep; Demir‐Cakan, Rezan; Kiskan, Baris; Yagci, Yusuf
Abstract: In this work, a new approach to vulcanize commercial poly(vinyl chloride) (PVC) at room temperature and in a relatively short time (4 h) by using elemental sulfur and an initiator such as Na2 S.9H2 O is reported. The obtained crosslinked polymer contains polysulfide linkages that facilitate recycling/self‐healing through dynamic S–S linkages. It is shown that PVC‐polysulfide networks could be reprocessed at 180 °C for three times. The thermal and spectral characterizations of the polymers before and after recycling are performed via FT‐IR, DSC, and TGA analyses. The potential use of the sulfur rich PVC‐polysulfide system as cathode material for Li‐S battery application is also investigated and the first discharge capacity is found to be around 610 mAh g −1 that later faded rapidly. Abstract : A new approach to vulcanize commercial poly(vinyl chloride) (PVC) at room temperature and in a relatively short time by using elemental sulfur and an initiator such as Na2 S.9 H2 O is reported. The obtained crosslinked polymer contains polysulfide linkages that facilitate recycling/self‐healing through dynamic S–S linkages. It is shown that PVC‐polysulfide networks could be reprocessed at 180 °C.